Strategy Analysis of Regional Tourism Development: Case Study of Restaurant in Barru District - Rita Rita; Muhammad Arifin (Publik : (Jurnal Ilmu Administrasi), 2020)
This study aims to describe the strategies used in increasing restaurant guest visits in Barru Regency. This research uses a quantitative descriptive approach. Based on the results of the study, it was found that the 4P marketing mix strategy (Price, Promotion, Place and position) was applied to the Barru district restaurant to increase guest visits, this proved effective in attracting guests to visit the restaurant. product, price, place, promotion, have shown conformity with the segmentation, targeting and positioning expected by the restaurant. For example, the products offered are varied and use quality raw materials in accordance with the positioning that the company wants to achieve as the only restaurant that uses healthy raw chicken and seafood. Apart from that the price, physical evidence and promotion are also in accordance with the targeting of young people and families, because the prices offered are still quite affordable, the place is also unique and is promoted through online media.